The Implementation Of Green Accounting And Corporate Social Responsibility On Company Value - Hizkia Immanuel Silitonga; Hisar Pangaribuan; Mila Susanti (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The purpose of this study is to examine how corporate social responsibility and green accounting affect the value of companies in the Heavy Construction & Civil Engineering subsector that are listed on the Indonesia Stock Exchange for the years 2021–2023. Purposive sampling is used in this study, and 20 businesses that fit the requirements are included. Descriptive statistical analysis, normality, multicollinearity, determination, partial, and simultaneous tests were used to assess the data. The study's findings show that, in contrast to corporate social responsibility, which has no discernible impact on firm value, green accounting has a substantial impact. Nonetheless, social responsibility and green accounting both have a big impact on a company's worth.